The Mitigation of Risk Management: Non-Productive Time Analysis on Drilling Operations in ZY Field - Muhammad Ariyon; Rahman, Bobby; Sastraningsih, Ellyan; Mayes, Anthony (UIR PRESS, 2024)
Currently, petroleum is still the main energy source in Indonesia. However, since the 1990s, Indonesia began to experience a decline in oil production and an increase in domestic energy demand, which caused Indonesia to import oil to meet domestic energy needs. Through SKK Migas, Indonesia has a target to produce 1 million barrels per day by 2030, with one of the efforts being undertaken by carrying out massive and aggressive drilling. Drilling is the most critical, dangerous, complex and expensive operation in the oil and gas industry. It cannot be denied that in reality many unplanned problems (unscheduled events) which result in non-productive time (NPT) are encountered during drilling operations which sometimes cause unpredictable budget usage and can also result in delays in hydrocarbon production. This research was carried out by analyzing 50 wells that had been drilled in the BR field. In this research, a risk management process was carried out for the NPT categories to determine the level of risk in each NPT category and develop a mitigation analysis to reduce the NPT. Dealing with the finding, it indicates that the NPT rig moving (RMV) and drilling 8-1/2 (DRLG 8-1/2) categories have a red risk level which means unacceptable. The biggest contribution to NPT in the RMV category is location problems, while for DRLG 8-1/2 it is loss of circulation